CD180 expression in B‐cell lymphomas: A multicenter GEIL study. Issue 5 (6th October 2015) - Mayeur‐Rousse, Caroline; Guy, Julien; Miguet, Laurent; Bouyer, Sabrina; Geneviève, Franck; Robillard, Nelly; Solly, Françoise; Maar, Aida; Bené, Marie C; Mauvieux, Laurent; ,
Abstract : CD180, a related member of the Toll‐like receptor family, is lost or underexpressed at the plasma membrane in circulating cells of various B‐cell lymphomas except marginal zone lymphomas (MZL). In order to confirm its clinical relevance in routine analysis, we evaluated prospectively the expression of CD180 in 236 patients from 5 French University Hospital laboratories on behalf of the GEIL. Highly comparable results were obtained in all centers using the EuroFlow standardization protocol. We observed that CD180 median fluorescence (MdFI) was significantly higher in MZL and hairy cell leukaemia (HCL) compared to all other B‐cell proliferations ( P < 0.05). CD180 intensity could distinguish lymphomas with numerous villous lymphocytes from other MZL. ROC curve analysis identified a CD180 MdFI threshold for which the diagnosis of MZL could be assessed with 77% sensitivity and 92% specificity. This study showed that CD180 can be considered as a single positive robust marker of MZL and should be therefore included in flow cytometry panels for the diagnosis of mature B‐cell neoplasms. Harmonization process is of great interest in order to evaluate new markers in multicentric studies and to set up decisional thresholds. © 2015 International Clinical Cytometry Society